A method based on the transmission line information for normal operation and fault of solving transfer impedance. Issue 1 (1st January 2022) - Li, Mengjiao; Yu, Haifeng; Xie, Yuzheng; Chen, Zehong; Li, Xinran; Lu, Chunjing
Abstract: Under the background of UHV project, the level of power system short-circuit current increasing has been one of the challenges of these power grid is facing. Therefore, it is necessary to analyze the characteristics of short-circuit current in power grid. The traditional method of calculating transfer impedance is to form node impedance matrix through network, and then calculate transfer impedance by formula. The precondition of the traditional method is to know the parameter information of each element in power grid, however, it is difficult to accurately give the parameter information of each element in engineering application. Based on the limitations of the traditional method, a method based on the transmission line information for normal operation and fault of solving transfer impedance is proposed, which treats the grid as a black box except for the short circuit point, so it is not necessary to know the parameter information of each element in the power grid as a known condition. Applying the method to solve for transfer impedance in a ring network, and the results are compared with the results of the traditional method to verify that the method is feasible.